Degradation of Benzo[a]pyrene by Mycobacterium vanbaalenii PYR-1 - Moody, Joanna D. (American Society for Microbiology, 2004)
Metabolism of the environmental pollutant benzo[a]pyrene in the bacterium Mycobacterium vanbaalenii PYR-1 was examined. This organism initially oxidized benzo[a]pyrene with dioxygenases and monooxygenases at C-4,5, C-9,10, and C-11,12. The metabolites were separated by reversed-phase high-performance liquid chromatography (HPLC) and characterized by UV-visible, mass, nuclear magnetic resonance, and circular dichroism spectral analyses. The major intermediates of benzo[a]pyrene metabolism that had accumulated in the culture media after 96 h of incubation were cis-4,5-dihydro-4,5-dihydroxybenzo[a]pyrene (benzo[a]pyrene cis-4,5-dihydrodiol), cis-11,12-dihydro-11,12-dihydroxybenzo[a]pyrene (benzo[a]pyrene cis-11,12-dihydrodiol), trans-11,12-dihydro-11,12-dihydroxybenzo[a]pyrene (benzo[a]pyrene trans-11,12-dihydrodiol), 10-oxabenzo[def]chrysen-9-one, and hydroxymethoxy and dimethoxy derivatives of benzo[a]pyrene. The ortho-ring fission products 4-formylchrysene-5-carboxylic acid and 4,5-chrysene-dicarboxylic acid and a monocarboxylated chrysene product were formed when replacement culture experiments were conducted with benzo[a]pyrene cis-4,5-dihydrodiol. Chiral stationary-phase HPLC analysis of the dihydrodiols indicated that benzo[a]pyrene cis-4,5-dihydrodiol had 30% 4S,5R and 70% 4R,5S absolute stereochemistry. Benzo[a]pyrene cis-11,12-dihydrodiol adopted an 11S,12R conformation with 100% optical purity. The enantiomeric composition of benzo[a]pyrene trans-11,12-dihydrodiol was an equal mixture of 11S,12S and 11R,12R molecules. The results of this study, in conjunction with those of previously reported studies, extend the pathways proposed for the bacterial metabolism of benzo[a]pyrene. Our study also provides evidence of the stereo- and regioselectivity of the oxygenases that catalyze the metabolism of benzo[a]pyrene in M. vanbaalenii PYR-1.